Paisaje, clima y carácter en De humana physiognomonia de Giovan Battista della Porta - González Manjarrés, Miguel Ángel (Espaços e Paisagens. Antiguidade Clássica e Heranças Contemporâneas)
The De humana physiognomonia written by Giovan Battista della Porta (ca. 1535-1615) became the definitive physiognomical manual that compiled, on the one hand, all the already existing theories in the discipline from Pseudo-Aristotle in the 3rd century bd. up to his period; and, on the other hand, the physiognomical doctrine of Hippocratic/Galenic roots. This work was first edited in 1586 in four books; it was extended into six books in 1601; finally, it was again extended and revised for its Italian version in 1610. The former has two chapters (in addition to references disseminated throughout the writing) which narrate how the place where one lives and the dominant climate there determine or, at least, condition the human character. Our aim here is to appreciate Della Porta’s elaboration of this topic and to analyse the literary structure that he uses for the writing.